GHOST - Swallow, James (London : Zaffre, 2018)
A terrible threat from the depths of the dark net. A devastating betrayal at the heart of a covert strike force. A deadly pursuit across a digital battlefield. A ruthless terrorist fuelled by revenge. As devastating attacks unfold across the globe, Marc Dane must call on all his skills and ingenuity to track down the mysterious figure behind it all - a faceless criminal known only as Madrigal. Before they plunge the world into war.
Includes an excerpt from "Nomad".
Keywords: English fiction; Intelligence officers -- Fiction; Conspiracies -- Fiction